Role of Bacterial Urinary Tract Infection in the Activity of Rheumatoid Arthritis - Rusul Hisham Ahmed; Ayaid Khadem Zgair (World Journal of Experimental Biosciences, 2022)
Rheumatoid arthritis (RA) is considered one of the most common autoimmune diseases in the world. The nature of this disease, as well as the medications used to treat it, contributes to the occurrence of various bacterial infections. The current study aims to determine the effect of bacterial urinary tract infections (UTI) on the activity of RA in terms of DAS28. In the present study, urine samples were collected from 70 patients suffering from RA and 30 healthy volunteers who did not suffer from RA. The bacterial isolates were isolated and identified using different enrich, selective, and differentiation media. Biochemical tests were also used to identify bacterial isolates. Bacterial diagnosis has been enhanced using VITIC technology. The study proved that the incidence of bacterial UTI patients with RA was higher than in the healthy control group who do not suffer from RA. The highest bacterial infection was found in the case of Staphylococcus aureus followed by Staphylococcus haemolyticus. While the lowest bacteria infection was found in the case of Klebsiella pneumoniae. There is no significant difference in the DAS28 of the cases (RA) infected with Escherichia coli, K. pneumoniae, Micrococcus luteus, S. aureus, S. epidermidis, Enterococcus faecium, and Streptococcus spp. The infection (UTI –RA) with S. haemolyticus involved with disease activity (high DAS28) P
Keywords: Bacterial infections, DAS 28, Rheumatoid arthritis, Urinary tract infection.